Liquid Soap Production from Pandan and Orange Raw Materials to Improve the Community's Economy - Ari, Ismu Rini Dwi; Anggraeni, Mustika Anggraeni; Yudono, Adipandang; Utomo, Dadang Meru; Hariyani, Septiana; Irawan, Annisa Triana; Hadianur, Muhammad Pavian Ariel; Zuldi, Rivaldhi Van (TEKAD : Teknik Mengabdi, 2026)
The production of liquid soap using natural raw materials such as pandan leaves and citrus fruits is an innovative effort to utilize local resources with the potential to improve the community’s economy. Pandan and citrus contain beneficial natural compounds, including distinctive aromas, antibacterial properties, and antioxidants, making them suitable ingredients for environmentally friendly personal care products. This activity aims to provide knowledge and practical skills to the community in processing natural materials into marketable liquid soap products, while also creating opportunities for small-scale household enterprises. The methods applied include raw material extraction, liquid soap formulation, as well as training in product packaging and marketing. The results indicate that liquid soap made from pandan and citrus has good quality, is safe for use, and is well accepted by consumers due to its natural ingredients and fresh fragrance. Furthermore, this activity enhances community creativity, self-reliance, and income. Therefore, the production of liquid soap based on pandan and citrus can serve as a sustainable alternative business that supports community economic development through the utilization of local potential.